Dufour and Soret effects on Darcy-Forchheimer flow of second-grade fluid with the variable magnetic field and thermal conductivity. Issue 9 (2nd January 2020) - Khan, Ambreen A.; Naeem, S.; Ellahi, R.; Sait, Sadiq M.; Vafai, K.
Abstract : Purpose: This study aims to investigate the effect of two-dimensional Darcy-Forchheimer flow over second-grade fluid with linear stretching. Heat transfer through convective boundary conditions is taken into account. Design/methodology/approach: Nonlinear coupled governing equations are tackled with a homotopy algorithm, while for numerical computation the computer software package BVPh 2.0 is used. The convergence analysis is also presented for the validation of analytical and numerical results. Findings: Valuation for the impact of key parameters such as variable thermal conductivity, Dufour and Soret effects and variable magnetic field in an electrically conducted fluid on the velocity, concentration and temperature profiles are graphically illustrated. It is observed from the results that temperature distribution rises by Dufour number whereas concentration distribution rises by Soret number. The Forchheimer number and porosity parameter raise the skin friction coefficient. The permeable medium has a vital impact and can help in reining the rate of heat transfer. Practical implications: The permeable medium has a vital impact and can help in reining the rate of heat transfer. Originality/value: To the best of the authors' knowledge, this study is reported for the first time.